Synthesis and biological activity evaluation of novel 2,6,9-trisubstituted purine conjugates as potential protein kinases inhibitors - Vlková, Kristýna; Gucký, Tomáš; Peřina, Miroslav; Řezníčková, Eva; Kryštof, Vladimír (Bioorganic & medicinal chemistry letters, 2022)
Deregulation of protein kinases is often associated with uncontrolled cell proliferation in various tumours and the inhibition of kinase activity remains an important target for anti-tumour drug development. Here, we report a novel series of 2-aminocyclohexylamino-6-(substituted benzylamino/anilino)-9-cyclopentylpurine derivatives conjugated with putrescine, spermidine or spermine moiety in an effort to expand library of highly potent 2,6,9-trisubstituted purine kinase inhibitors. Presented aniline-type conjugates exhibit significant cytotoxic activity in MV4-11 and EOL-1 cell lines which correlates with FLT3-ITD and PDGFRα inhibition. Furthermore, 6-anilinopurines affected MAPK and STAT pathways in the treated MV4-11 cells and induced cell cycle arrest in the G1 phase. 6-Benzylaminopurines showed comparable CDK2 inhibitory activity to 6-anilinopurines, however, the PDGFRα and FLT3-ITD inhibition was strongly suppressed. Our results show that novel compounds containing aniline in the structure can be involved in the development of potent tyrosine kinase inhibitors with strong activity toward acute myeloid leukemia or chronic eosinophilic leukemia.
Keywords: proliferace buněk; vztah mezi dávkou a účinkem léčiva; inhibitory proteinkinas; Cell Line, Tumor; screeningové testy protinádorových léčiv; puriny; Molecular Structure; Structure-Activity Relationship; lidé; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; proteinkinasy; protinádorové látky; Antineoplastic Agents; molekulární struktura; Dose-Response Relationship, Drug; Protein Kinase Inhibitors; Purines; Cell Proliferation; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; Protein Kinases; nádorové buněčné linie; Humans